Chorea: An unusual manifestation of endocrine diseases - Zheng, Jia; Wu, Xiaohong (Frontiers in Endocrinology, 2023)
Chorea is a movement disorder involving involuntary movements of muscles of the face, neck, and limbs, usually caused by basal ganglia lesions. As an important part of the presentation of many neurological diseases, chorea is also an unusual manifestation of endocrine diseases and can be challenging to diagnose. Although the most common etiology of chorea is genetic, it is vital to identify acquired or symptomatic chorea, as these are potentially treatable conditions. This review summarizes the latest developments in various endocrine disease-related chorea, which will help clinicians to correctly identify and accurately treat it.